PEMANFAATAN SAMPAH ORGANIK DAN TANAMAN LOKAL MENJADI ECO-ENZYME BAGI MASYARAKAT DESA LUMBAN PEA TIMUR BALIGE - Helena Tatcher Pakpahan; Lince Romauli Panataria; Jones T. Simatupang; Ebsan Marihot Sianipar (Universitas Methodist Indonesia, 2022)
Community Service (PkM) is carried out by the Faculty of Agriculture, Universitas Methodist Indonesia by providing organic farming counseling and training on the manufacture of eco-enzymes from vegetable, fruit and local plant waste for the community, especially farmers. PkM was held on June 9, 2022 in Lumban Pea Timur Village, Balige District, Toba Regency, North Sumatera Province. The method used is to conduct organic farming counseling as well as training to make eco-enzymes by utilizing waste materials from vegetables, fruits and local plants. This is a solution to the problems and constraints faced by farmers in the form of decreasing soil quality due to the use of inorganic fertilizers. At the time of providing counseling, it was explained that there was a decrease in soil quality due to the application of inorganic fertilizers that had been carried out in the long term. Likewise, the explanation of efforts to fix and improve soil quality through the provision of eco-enzymes. The results of PkM with organic farming counseling are very effective considering that there are still many farming communities who do not understand that it is necessary to improve and maintain soil quality by using eco-enzymes. With the existence of organic farming counseling as well as the manufacture of eco-enzymes, the farming community becomes aware of efforts to improve the soil and what benefits can be obtained by making eco-enzymes. Thus, it is hoped that the Lumban Pea Timur farmer community will always be motivated to improve and maintain soil quality independently by utilizing vegetable, fruit and local plant waste materials.